THE INFLUENCE OF FINANCIAL KNOWLEDGE, HEDONIC LIFESTYLE AND FINANCIAL TECHNOLOGY ON FINANCIAL BEHAVIOR - Yasir Maulana; Reyhan Alfarizi; Disman (PRODI BISNIS DIGITAL FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS KUNINGAN, 2026)
This study aims to test the influence of financial knowledge, hedonistic lifestyle, and financial technology on financial Behavior. This study uses a quantitative descriptive research method. The sample in this study consisted of 98 students from Kuningan University. The data collection technique employed a questionnaire, and the measurement used an interval scale. Data analysis employed multiple regression analysis. The results of the study from the proposed hypothesis concluded that: Financial Knowledge, Hedonistic Lifestyle and Financial Technology together affect Financial Behavior. Financial Knowledge has a positive and significant effect on Financial Behavior. Hedonistic Lifestyle has a positive and significant influence on Financial Behavior. Financial Technology has a positive and significant influence on Financial Behavior. These findings imply that cognitive factors, lifestyle characteristics, and technological adoption jointly shape students’ financial decision-making. The study highlights the importance of improving financial literacy and promoting responsible use of financial technology to support healthier financial Behavior.